Steel slag asphalt mixtures: a comprehensive analysis of performance enhancement mechanisms and environmental impact benefits - Linjie Yu; Bin Lei; Hanbing Zhao; Chaofeng Liang; Wengui Li (Environment, Development and Sustainability, 2026)
The shortage of high-quality natural aggregates and the accumulation of industrial solid waste have severely restricted the sustainable development of conventional asphalt pavement. The utilization of steel slag aggregate, a by-product of steelmaking, as a replacement for natural aggregate in asphalt pavement offers significant environmental benefits. Nevertheless, a systematic understanding of the application of steel slag in asphalt mixtures remains limited. In particular, research on the mechanisms underlying effects on pavement performance and a comprehensive assessment of environmental benefits is still insufficient. Accordingly, this study aims to exhaustively review research on the incorporation of steel slag in asphalt mixtures, encompassing the chemical and physical properties, mixture proportion design, pavement performance, and mechanical and functional properties. Additionally, based on the life cycle assessment theory, this paper discusses the benefits of steel slag’s Environmental Impact (EI) in Permeable Asphalt Mixtures (PAM). The results indicate that incorporating steel slag can significantly enhance the road performance, mechanical properties, and thermal-electrical conductivity of asphalt mixtures. Furthermore, all eight EI indicators of steel slag PAM, particularly for the specimen 100%SSA, decreased to varying degrees compared to conventional PAM. The relevant research findings are expected to provide theoretical support for the resource valorization of steel slag in asphalt pavements.